The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1124/dmd.110.032201
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1A2 Detoxicates Aristolochic Acid in the Mouse

Abstract: ABSTRACT:Aristolochic acids (AAs) are plant-derived nephrotoxins and carcinogens responsible for chronic renal failure and associated urothelial cell cancers in several clinical syndromes known collectively as aristolochic acid nephropathy (AAN). Mice provide a useful model for study of AAN because the renal histopathology of AA-treated mice is strikingly similar to that of humans. AA is also a potent carcinogen in mice with a tissue spectrum somewhat different from that in humans. The toxic dose of AA in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 29 publications
5
58
0
Order By: Relevance
“…30 Consequently, AA-I demethylation, mediated by Cyp1A2 is a primary pathway of AA-I detoxication. 28,30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Consequently, AA-I demethylation, mediated by Cyp1A2 is a primary pathway of AA-I detoxication. 28,30 …”
Section: Resultsmentioning
confidence: 99%
“…As stated above, the most important human and rat enzymes activating and detoxicating AA-I in liver are NQO1, CYP1A1 and CYP1A2. 15,27,29,30 …”
Section: Resultsmentioning
confidence: 99%
“…Gene-targeted mouse models confirm the role of hepatic cytochrome P-450 enzymes in detoxifying AA in vivo (69 -71). In the mouse, the primary CYP that metabolizes AAI is CYP1A2 (48), and human CYP1A2 is kinetically competent to metabolize AAI as well. Although a pilot genetic study found a potential link of the Cyp3A5*1 allele with BEN (6), CYP3A5 does not metabolize AA in vitro (48,53).…”
mentioning
confidence: 99%
“…In the mouse, the primary CYP that metabolizes AAI is CYP1A2 (48), and human CYP1A2 is kinetically competent to metabolize AAI as well. Although a pilot genetic study found a potential link of the Cyp3A5*1 allele with BEN (6), CYP3A5 does not metabolize AA in vitro (48,53). Other studies have failed to establish a genetic link between known functional alleles in several CYPs, nitroreductases, or phase II genes and BEN (5,6,64).…”
mentioning
confidence: 99%
“…In humans, CYP2C9 is reported to be the major AA-metabolizing enzyme, beside CYP1A1 and CYP1A2, which also have a robust AAI demethylating activity. 36 Acetyl-CoA-acyltransferase (Acaa1) was also reported to predict renal insult induced by different nephrotoxic compounds, including cadmium. 29 The fact that several drug-metabolizing enzymes, such as a-GST and p-GST, were also included into the urinary biomarker panel shows the important role of this class of enzymes in acute drug-induced tissue responses and in their potential to detect acute cellular changes.…”
Section: Discussionmentioning
confidence: 99%